Pyeloplasty is a safe and effective surgical approach for low functioning kidneys with ureteropelvic junction obstruction. Issue 2 (April 2021) - Bowen, Diana K.; Mittal, Sameer; Aghababian, Aznive; Eftekharzadeh, Sahar; Dinardo, Lauren; Weaver, John; Long, Christopher; Shukla, Aseem; Srinivasan, Arun K.
Summary: Introduction: Indications for treatment of ureteropelvic junction obstruction (UPJO) include symptomatic obstruction, urinary tract infections, presence of an obstructive pattern on functional renal scan and/or worsening differential renal function (DRF). This paper aims to determine the relationship between preoperative DRF and surgical outcomes after pyeloplasty. We hypothesized that low preoperative DRF is not an independent predictor of pyeloplasty failure. Methods: A retrospective chart review was performed to identify all patients undergoing pyeloplasty for UPJO between 2008 and 2019. Patients were included only if they had at least one preoperative functional scan and a minimum of one renal ultrasound post-operatively. Patients were divided into three groups based on DRF for analysis: Group 1- 0-10%, Group 2 - >10-≤20%, Group 3 - >20%. Baseline, intraoperative and postoperative characteristics, including success and complications were compared. Additional sensitivity analyses were performed comparing patients with ≤20%, and >20% function, ≤30%, and >30% function as well as an analysis of patients undergoing only minimally invasive reconstruction. Results: Three hundred and sixty-four patients met inclusion criteria. We identified 8 patients in Group 1, 24 patients in Group 2 and 332 patients in Group 3. Mean procedure time was longest for the ≤10% function group (237.9 vs 206.4 vs 189.1; p = 0.01). We found no difference in 30-day post-operative complications, overall success rate or the need for additional procedures among the three groups. For patients in Group 1, we noted variation in the post-procedure DRF with a range of −2.8 to +47% change. In this group, none of patients with low DRF underwent nephrectomy. Multivariate logistic regression did not identify renal function as a predictor of operative success OR 1.00 (95% CI: 0.97–1.03) (p-value: 0.88). Discussion: The results of the present study suggest that low DRF alone is not associated with worse outcomes and shows no difference in the failure rate. The incidence and type of complications were not increased for the lower functioning groups. The main limitation of this study would be its retrospective nature and single-institution experience. Furthermore, post-operative functional studies were not available for all patients, limiting the ability to draw conclusions on the change in DRF after surgery. Conclusions: In a large cohort, preoperative DRF was not predictive of pyeloplasty success rate. DRF ≤10% was not associated with higher incidence of complications or failure rate. The DRF alone should not dictate the management options available for patients with UPJO. Summary Table Surgical outcomes after pyeloplasty categorized by baseline renal function. Summary Table Factor, N (%) Preoperative renal function p-value Group 1 0-10% Group 2 >10% - ≤20% Group 3 >20% N 8 24 332 Technique 0.40 Robotic-Assisted 8 (100.0%) 19 (79.2%) 256 (77.1%) Open 0 (0.0%) 4 (16.7%) 70 (21.1%) Laparoscopic 0 (0.0%) 1 (4.2%) 6 (1.8%) Post-operative Complications 1 (12.5%) 4 (16.7%) 51 (15.4%) 0.91 Grade 1 0 (0.0%) 2 (50.0%) 13 (25.5%) 0.75 Grade 2 1 (100.0%) 2 (50.0%) 23 (45.1%) Grade 3a 0 (0.0%) 0 (0.0%) 1 (2.0%) Grade 3b 0 (0.0%) 0 (0.0%) 13 (25.5%) Grade 4a 0 (0.0%) 0 (0.0%) 1 (2.0%) Overall success 8 (100.0%) 23 (95.8%) 311 (93.7%) 1.00 Asymptomatic after surgery 8 (100%) 23 (95.8%) 314 (94.6%) 1.00 Unimproved hydronephrosis 0 (0.0%) 1 (0%) 21 (6.3%) 0.72 Additional endoscopic procedure 0 (0.0%) 1 (4.2%) 19 (5.7%) 1.00 Underwent redo reconstruction 0 (0.0%) 1 (4.2%) 12 (4.2%) 1.00